Propiedades medicinales de especies forestales en cuatro comunidades rurales del Cantón Valencia, Provincia de Los Ríos. - Terán Montero, Jorge Arturo (2013)
The research was conducted in four rural communities in the canton Valencia, province of Los Ríos. The communities studied were : Six August , Mirador de Valencia, Copal and Toachi Union . Due to the nature and characteristics of research , this study is non-experimental design, because the research process has not been any kind of intentional manipulation of variables , so that the phenomenon is observed as presented in the context , therefore , no situation is not built. For data collection instruments such as questionnaire, which the general population of each community studied (122 people) went and consisted of 15 questions were used. This experimental study was scientific. The species that we identified in the communities were: fruit bread, (Artocarpus altilis), Beldaco (Pseudobombax millei), Sangre de Drago (Dialyanthera gordoniaefolia), Álamo (Populus sp.), Matapalo (Ficus jacobii), Sangre de Gallina (Vismia obtusa), Cojojo (Acnistus arborescens), Tillo (Brosimum alicastrum), Abejón (Senna didymobotrya), Sande (Brosimum utile), Achiote (Bixa orellana) y Copal (Dacryodes peruviana). They have also been used to cure diseases such as: Urinary tract , skin, hemorrhoids, cholesterol and gases. Less common uses are: douche, snakebite and healing